2005
DOI: 10.1021/jf049048c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Soybean Oil on Conjugated Linoleic Acid Content in Beef

Abstract: Forty-eight steers were used to study the influence of feeding soybean oil (SO) on the conjugated linoleic acid (CLA) content of beef. Steers were fed either a control diet containing 954 g/kg of dry matter (DM) corn-based concentrate (CTL) or a control diet supplemented with SO at 20 (SO2) or 40 g/kg (SO4) of diet DM for 105 days. Adipose tissue samples were collected from the M. longissimus dorsi (LD) and from the M. semitendinosus (ST) on days 0 and 63 of the experiment. Adipose and muscle tissue samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(61 reference statements)
3
23
1
5
Order By: Relevance
“…This enzyme partly converts the 18:0 into c 9-18:1 in the adipose tissue (Demeyer and Doreau, 1999) and its activity is inhibited by PUFAs (Ntambi, 1999), which were more abundant in the SOY treatment. Similar results have been reported by Dhiman et al (2005) with 4% soybean oil, and Madron et al (2002) with extruded whole seed soybean. Although the OLI diet provides a greater amount of c 9-18:1 than the PALM diet (Table 2), the content of this FA in the OLI meat fat did not differ from that of the PALM meat fat.…”
Section: Meat Qualitysupporting
confidence: 89%
“…This enzyme partly converts the 18:0 into c 9-18:1 in the adipose tissue (Demeyer and Doreau, 1999) and its activity is inhibited by PUFAs (Ntambi, 1999), which were more abundant in the SOY treatment. Similar results have been reported by Dhiman et al (2005) with 4% soybean oil, and Madron et al (2002) with extruded whole seed soybean. Although the OLI diet provides a greater amount of c 9-18:1 than the PALM diet (Table 2), the content of this FA in the OLI meat fat did not differ from that of the PALM meat fat.…”
Section: Meat Qualitysupporting
confidence: 89%
“…Duckett et al (2002) fed steers a diet with 80% conventional corn and found a greater duodenal flow of VA than t10-18:1. The amount of VA increased when high-oil corn was substituted for conventional corn, but when corn oil was added to conventional corn at the same rate as in the high-oil corn, the flow of t10-18:1 was more than 300% higher than the flow of VA. Beaulieu et al (2002) and Dhiman et al (2005) added soybean oil to a corn-based diet and found greater concentrations of total trans-18:1 in adipose tissue, but no change was observed in RA, leading them to speculate the increase in trans fatty acids was related to isomers other than VA. When Madron et al (2002) supplemented a corn-based diet with up to 25.6% extruded full fat soybeans, however, muscle concentrations of t10-and t11-18:1 increased, but VA remained the predominant isomer.…”
Section: Pufa In Low Forage-to-concentrate Ratio Diets Can Be a Bad Cmentioning
confidence: 99%
“…The other main isomer of synthetic CLA, trans-10,cis-12, is present in food in negligible amounts. Thus this isomer is considered to be 'man-made' and may not have much relevance if CLA is obtained from natural sources (Chin et al, 1994;Dhiman et al, 2005;Park & Pariza, 1998). Currently, most CLA research reports on the activities of these two isomers.…”
Section: Isomers Of Clamentioning
confidence: 99%